Positivism and liberalism: On Some Sources of the Czech Philosophy of History of the 19th Century - Loewenstein, Bedřich (Dějiny – teorie – kritika, 2023)
We often use the term "positivism" imprecisely, in the sense of scientific distaste for philosophical generalisation. Here I wish to attempt a reconstruction of the intellectural historical background to the origins and character of West European positivism. The experience of the French Revolution, denounced by its critics as the result of the Enlightenment theories, played a major role in the emergence of the tradition. Scientific demonstration (i. e. proof free of metaphysical speculation) of the inevitability of progress was seen as a way of ensuring that society avoided bling alleys – the terror of military despotism but also aristocratic reaction. The idea was that historical events, only superficially a mass of accidents and caprice, were in fact governed by laws as inexorable as those of the natural non-human world. Early positivist thought was motivated by this basic impulse, as can be shown in the histories of the French Revolution that are characterised in the first part of the essay. The classic works of positivist historical philosophical and sociological thinkers that are the subject of the second part of the essay are also ideological in the sense that they arise from period needs and interest in overcoming social crisis and scientifically demonstrating that progress was not just meaningful but unstoppadle. The weaknesses of the concepts and arguments employed, today very obvious, were to some extent already clear to John Stuart Mill, who applied a series of liberal corrections to the Comte´s version of the theory of inevitable social development. Both variants of positivism played a fundamental role in forming the historical thought of T. G. Masaryk, but the concepts of the French historians were also a discernible inspiration in Czech historiography.